2022
DOI: 10.1007/s40258-022-00754-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Health Inequality in Five Caribbean Basin Countries Using EQ-5D-5L

Abstract: Background EQ-5D-5L is a standardized health outcomes instrument that can be added to national surveys to measure inequality in health outcomes. The aim of this study was to produce baseline values of health inequality using EQ-5D-5L for five countries in the Caribbean Basin region based on national surveys in 2012-2014. Methods The EQ-5D-5L questionnaire was included in adult population surveys of Barbados, Belize, Colombia, Jamaica and Trinidad and Tobago. EQ-5D-5L measures were calculated for demographic gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
5
0
2
Order By: Relevance
“…Our results are in line with previous findings using the one-dimension self-rated health question (4) showing variation in inequalities in health associated with socioeconomic status across European countries. The successful application of the EQ-5D (both 3L or 5L) in socio-demographic analyses in selected countries and regions were also confirmed by several other recent studies (36)(37)(38)(39), and in vulnerable groups like homeless persons (40). Specifically, Sronk et al showed that among three European countries the EQ-5D-5L was able to detect education level related inequalities in health, however, differences varied across countries and some of the impact was canceled out when controlling for chronic conditions and ability to work.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Our results are in line with previous findings using the one-dimension self-rated health question (4) showing variation in inequalities in health associated with socioeconomic status across European countries. The successful application of the EQ-5D (both 3L or 5L) in socio-demographic analyses in selected countries and regions were also confirmed by several other recent studies (36)(37)(38)(39), and in vulnerable groups like homeless persons (40). Specifically, Sronk et al showed that among three European countries the EQ-5D-5L was able to detect education level related inequalities in health, however, differences varied across countries and some of the impact was canceled out when controlling for chronic conditions and ability to work.…”
Section: Discussionsupporting
confidence: 74%
“…This was the case even after taking into account health related behaviors and conditions (37). A study from five Caribbean countries used odds ratios and concentration indices to detect education and income related inequalities with the EQ-5D-5L and also found significant inequalities that varied across countries (38). Studies using the EQ-5D-3L provided similar evidence of detecting income related health inequalities in low income communities (39), and high reported problems among homeless people (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many cross-country papers that focus on the relationship between income inequality and average health status. For example, the negative effect of income inequality on average health status is shown to be larger in countries characterised by market-based more than community-based health-care strategies [ 67 ], a larger range of age and gender inequality [ 68 , 69 ], a larger range of relative poverty [ 70 ], a larger range of absolute poverty [ 71 ] or a less efficient health-care system [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pero como dichos puntajes fueron calculados para el Reino Unido y tienen más de una década de antigüedad, decidimos ajustarlos de manera que reflejen mejor la realidad actual de República Dominicana. Para ello utilizamosBailey et al (2022), que calcula los pesos de calidad de vida para cinco países del Caribe: Barbados, Belice, Colombia, Jamaica y Trinidad y Tobago. Lamentablemente, las ponderaciones resultantes se encuentran demasiado agregadas para poder hacer buenos ajustes.…”
unclassified